Vision and transformation : an introduction to the Buddha's noble eightfold path - Sangharakshita (Birmingham : Windhorse Publication., 1995)
The Eightfold Path is the most widely known formulation of the Buddha's teaching. It is ancient, reaching back to the Buddha's very first discourse, and it is highly venerated as a treasury of wisdom and practical guidance. Like the teaching itself, this work covers every aspect of life.
Includes index.
Keywords: Buddhism -- Doctrines